STRATEGI PENANGANAN KAWASAN PEMUKIMAN KUMUH DI KELURAHAN TANAH DATAR KECAMATAN PEKANBARU KOTA KOTA PEKANBARU - Dewi Marni; Sofyan Husein Siregar; Imam Suprayogi (Jurnal Ilmu Lingkungan, 2020)
The development of slums in urban areas is inseparable of the increases in population and population activity. In addition, undirected and unplanned development also supports the degradation of the quality of residential environment. One area that is included in the slum area is located in Tanah Datar Sub-District. The residential area of Tanah Datar Sub-District is right in the heart of Pekanbaru city. Thus, living conditions and the welfare of the people who live in these settlements greatly affect the face of a city. The characteristics and conditions of slums in each region is different. Thus, this study aims to identify the condition of a residential area in order to determine alternatives to handling slum areas appropriately. The method used  is exploratory descriptive of phenomena and facts relating to the condition of the community and the environment of slum areas based on real facts, expert opinion and the criteria of the Minister of PUPR Regulation Number 14/PRT/M/2018. The results showed that in achieving the goal of handling slum areas, the priority of government policy and budget allocation alignments be the most important factor. Then, strengthen government collaboration with relevant stakeholders and  handling based on the priority scale required by the residential area.